How Do Capital Requirements Affect Loan Rates? Evidence from High Volatility Commercial Real Estate* - Glancy, David; Kurtzman, Robert (The Review of Corporate Finance Studies, 2022)
Abstract We investigate how capital requirements affect loan rates by studying the 50% increase in the risk weight for high volatility commercial real estate (HVCRE) loans under Basel III. Exploiting variation in loan terms and exposure to the period after the rule’s implementation, we find that a one-percentage-point increase in capital requirements raises loan rates by 8.5 basis points. Using a model of bank funding costs, we demonstrate the timing and scope of the HVCRE rule implies our estimate reflects the steady-state cost of capital requirements. (JEL G21, G28, G38)